Mating experience and juvenile hormone enhance sexual signaling and mating in male Caribbean fruit flies - Teal, P. E. A. (The National Academy of Sciences, 2000)
Young mated male Caribbean fruit flies [Anastrepha suspensa (Loew)] have greater sexual prowess than their virgin counterparts. After mating for the first time, 6- to 7-day-old males released twice as much sex pheromone and acquired another mate in less than half the time required by virgin males of the same age. Mass spectroscopic analysis of extracts of hemolymph from mated and virgin 7-day-old males resulted in identification of juvenile hormone III bisepoxide and juvenile hormone III in a ratio of 2.5:1. Extracts from mated males contained 3-fold more juvenile hormone than did extracts from virgins. Enhancement of sexual signaling, pheromone release, and mating was induced by topical application of juvenile hormone, methoprene, or fenoxycarb. Newly eclosed adult males treated with juvenoids engaged in sexual signaling, released pheromone, and mated at significantly earlier ages than control males. We conclude that juvenile hormone mediated a positive feedback system that imparted a competitive advantage, guaranteeing that males who mated at an early age would out-compete virgins of the same age for mating opportunities. Additionally, the results support the hypothesis that juvenile hormone is a pivotal hormone coordinating the development of sexual signaling and reproductive maturity in these flies.